THE EFFECT OF GIVING DRAGON FRUIT (Hylocereus polyrhizus) JUICE THROUGH DRINKING WATER ON FAT DISTRIBUTION OF MALE BALI DUCKS - N.K.D.,, Sukreni,; Puspani,, E.; Wibawa., A.A.P.P. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
This study aims to determine the effect of giving dragon fruit peel ( Hylocereus polyrhizus ) juice through drinking water on the fat distribution of male Balinese ducks.  The research was located at Jl. Br. Tengah Gulingan, Badung Regency, Bali. The research was conducted for 8 weeks, from August to October 2023. The design used was a completely randomized design (CRD) consisting of 4 treatments and 5 replications.  Each experimental plot was filled with 3 DODs of Bali Janta ducks.  The four treatments were male Balinese ducks given drinking water without dragon fruit skin juice as control (P0), drinking water with 6% dragon fruit skin juice (P1), drinking water with 8% dragon fruit skin juice (P2), and drinking water with 10% dragon fruit skin juice (P3).  The variables observed were fat pads, mesentery fat, gallbladder fat, and abdominal fat.  The results showed that P1, P2 and P3 had a significant effect (P <0.05) on cushion fat, mesentery fat, gallbladder fat and abdominal fat.  Based on the results of this study it can be concluded that the administration of dragon fruit peel juice with levels of 6%, 8% and 10% can reduce the percentage of cushion fat, mesentery fat, gallbladder fat and abdominal fat of male Balinese ducks.